Purification and characterization of three soluble invertases from barley (Hordeum vulgare L.) leaves. - Obenland, D M (1993)
Three soluble isoforms of invertase (beta-fructofuranosidase; EC 3.2.1.26) were purified from 7-d-old primary leaves of barley (Hordeum vulgare L.). Invertase I, a monomeric protein of 64 kD, was purified to apparent homogeneity as shown by sodium dodecylsulfate-polyacrylamide gel electrophoresis. Invertases IIA and IIB, multimeric proteins with molecular masses of the 116 and 155 kD, were purified 780- and 1370-fold, respectively, but were not yet homogeneous. Extracts of epidermal strips of leaves contained only invertase IIB. The specific activity of invertase was more than 100-fold higher in the epidermis than in the mesophyll. All three isoforms were acidic invertases, with pH optima of around 5.0 and little activity in the alkaline range. Invertase I had a Km for sucrose of 8.1 mM, and invertases IIA and IIB had much lower values of 1.0 and 1.7 mM, respectively. Invertase I was more than 2-fold more resistant than the other two invertases to the inhibitors HgCl2 and pyridoxal. All three constitutive invertases were found to act also as sucrose-sucrose fructosyltransferases when supplied with high concentrations of sucrose, forming 1-kestose as principal product. However, the fructosyltransferase activity of all three enzymes was inhibited by pyridoxal in the same way as their invertase activity. This characteristic clearly differentiates them from the inducible sucrose-sucrose fructosyltransferase of barley leaves, the activity responsible for the initial steps of fructan biosynthesis, which has previously been shown to be insensitive to pyridoxal.